Impact of Psychological Factor in Grahani Roga - Mishra, Rakesh; Mishra, Ankita; Kotturshetti, IB (International Research Journal of Ayurveda & Yoga, 2022)
Grahani roga is the most common infection of gastro-digestive system and seen regularly in everyday practice. In our works of art Grahani is depicted as an Agni adhishthana. Any unsettling influence in the situation with agni prompts Grahani roga. Grahani roga is one among the Ashtamahagadas. Ayurveda depicted the distinction of Mana and Shareera and their indistinguishable and associated connection in the body. In Ayurveda separate Nidana panchakas are not clarified for Grahani roga, as Samanyanidana is material and mental variable of Grahani roga in general. Grahani roga is a prevalent Pitta Vatadosha and the mental element can be effectively be upset by Vata and Pitta Dosha. Both Ayurveda and contemporary science acknowledge the way that for better administration and avoidance of Grahani roga (IBS,) mental variables are playing a huge part. So to eliminate an infection from its root, the causative elements ought to likewise be perceived and precluded totally. With the thought of expanding rate gastro-digestive illness across the globe and world is looking forward towards Ayurveda for safe treatment modalities, it is fundamental for discover the viable helpful strategies from our science. In this article a work is made to comprehend the job of mental component in Grahani roga.